Macular Vascular Geometry Changes With Sex and Age in Healthy Subjects: A Fundus Photography Study - Feng, Ziqing; Wang, Gengyuan; Xia, Honghui; Li, Meng; Liang, Guoxia; Dong, Tingting; Xiao, Peng; Yuan, Jin (Frontiers in Medicine, 2021)
PURPOSE. To characterize the sex and age-related alterations of macular vascular geometry in a population of healthy eyes using fundus photography. METHODS. A cross-sectional study was conducted with 610 eyes from 305 healthy subjects (136 males, 169 females) who underwent fundus photography examination and were divided into four age groups (G1 with age ≤25 years, G2 with age 26 ~ 35 years, G3 with age 36 ~ 45 years, and G4 with age ≥46 years). A self-developed automated retinal vasculature analysis system allowed segmentation and separate multi-parametric quantification of the macular vascular network according to Early Treatment Diabetic Retinopathy Study (ETDRS). Vessel fractal dimension (Df), vessel area rate (VAR), average vessel diameter (Dm), and vessel tortuosity (𝞽n) were acquired and compared between sex and age groups. RESULTS. There was no significant difference between the mean age of male and female subjects (32.706±10.372 and 33.494±10.620, respectively. P>0.05) and the mean age of both sex in each age groups (P>0.05). The Df, VAR and Dm of the inner ring, the Df of the outer ring, and the Df and VAR of the whole macula were significantly greater in male than female (P<0.001, P<0.001, P<0.05 respectively). There was no significant change of 𝞽n between male and female (P>0.05). The Df, VAR and Dm of the whole macula, inner and outer rings associated negatively with age (P<0.001), whereas the 𝞽n showed no significant association with age (P>0.05). Comparison between age groups observed that Df started to decrease from G2 compared to G1 in the inner ring (P<0.05) and Df, VAR and Dm all decreased from G3 compared to younger groups in the whole macula, inner and outer rings (P<0.05). CONCLUSIONS. In healthy subjects, macular vascular geometric parameters obtained from fundus photography showed that Df, VAR and Dm are related to sex and age while 𝞽n is not. The baseline values of macular vascular geometry were also acquired for both sex and all the age groups.